Uranium mining and sense of community in the Great Karoo: Insights from local narratives. Issue 1 (January 2019) - Issah, Moshood; Umejesi, Ikechukwu
Highlights: The proposed uranium mining project will cause influxes of migrants into the region. The proposed uranium mining project will threaten physical security in the region. The proposed uranium mining project will alter social dynamics of the region. The proposed uranium mining project will affect the available infrastructures in the region. The proposed uranium mining project will bring the needed cultural diversity to the region. Abstract: Since the discovery of uranium in commercial quantities in the Great Karoo, plans have been in place to carry out large-scale uranium mining in the region. One of the justifications for doing so is the belief that it will catalyze socio-economic development in the region. However, some stakeholders have maintained that the proposed mining operations would threaten the social fabric of the communities in the Great Karoo region where the proposed mining operations will take place. The aim of this study is to broaden understanding of the likely impacts of the proposed mining activities on the social fabric of the surrounding communities in Beaufort West. Drawing on findgins from qualitative research, the study concludes that while the proposed mining will indeed alter the existing social fabric, it will also facilitate the human diversity required for addressing some of the developmental challenges the region faces